2023
DOI: 10.1007/s12664-022-01310-y
|View full text |Cite
|
Sign up to set email alerts
|

High seroprevalence against SARS-CoV-2 in non-vaccinated patients with inflammatory bowel disease from Northern India

Abstract: Background The information on seroprevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection among patients with inflammatory bowel disease (IBD) and its comparison to healthy controls is sparse. We compared the seroprevalence rates in patients with IBD and healthy controls (HCs). Methods Patients with IBD and HCs (contact of patients) underwent SARS-CoV-2 antibody testing (chemiluminescent immunoassay: Siemens kit IgG against antigen-S1RBD) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Patients with and without immunosuppressants had similar seroprevalence (32% vs. 27%, p > 0.05) and between patients with and without IBD (28.1% vs. 36%, p > 0.05). Indicating a high seroprevalence in patients with IBD from Northern India, up to 1/3 of IBD patients were seropositive for immunoglobulin G (IgG) SARS-Cov-2 antibodies [35]. In other investigations, researchers found that patients with IBD treated with the anti-TNF drug infliximab, which was linked to an increased risk of SARS-CoV-2 infection, had vaccine-induced antibody responses that were less robust and lasting than patients treated with the anti-integrin drug vedolizumab, which has a gut-specific mode of action and does not result in systemic immunosuppression.…”
Section: Examining the Connection Between The Pandemic Sars-cov-2 And...mentioning
confidence: 99%
“…Patients with and without immunosuppressants had similar seroprevalence (32% vs. 27%, p > 0.05) and between patients with and without IBD (28.1% vs. 36%, p > 0.05). Indicating a high seroprevalence in patients with IBD from Northern India, up to 1/3 of IBD patients were seropositive for immunoglobulin G (IgG) SARS-Cov-2 antibodies [35]. In other investigations, researchers found that patients with IBD treated with the anti-TNF drug infliximab, which was linked to an increased risk of SARS-CoV-2 infection, had vaccine-induced antibody responses that were less robust and lasting than patients treated with the anti-integrin drug vedolizumab, which has a gut-specific mode of action and does not result in systemic immunosuppression.…”
Section: Examining the Connection Between The Pandemic Sars-cov-2 And...mentioning
confidence: 99%